2021
DOI: 10.1002/aur.2514
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment in unmet healthcare and family support services: A survey of caregivers of children and youth with autism spectrum disorder in Delaware

Abstract: The study aimed to collect data from families of children and youth with Autism Spectrum Disorder (ASD) in the state of Delaware, USA to understand their ongoing needs and challenges in accessing child healthcare and family support services. We analyzed responses from 263 caregivers of children and youth with ASD from 3 to 24 years using a statewide needs assessment survey. Over 50% caregivers indicated having unmet needs relative to both child/youth healthcare services and family support services. Between 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 78 publications
1
16
0
3
Order By: Relevance
“…For example, demographic factors such as race/ethnicity, socio‐economic status (SES), insurance status, and geographic location may hinder their ability to gain knowledge about or utilize certain services (Liptak et al, 2008 ; Monz et al, 2019 ; Thomas et al, 2007 ). On the other hand, certain child‐related factors such as ASD/impairment severity (e.g., greater impairments in the social, language, behavioral, or motor domains) or age (e.g., younger children) may be related to greater service needs (Green et al, 2006 ; Srinivasan, Ekbladh, et al, 2021 ; White et al, 2006 ). Taken together, different child and family characteristics will influence service utilization by families of children with ASD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, demographic factors such as race/ethnicity, socio‐economic status (SES), insurance status, and geographic location may hinder their ability to gain knowledge about or utilize certain services (Liptak et al, 2008 ; Monz et al, 2019 ; Thomas et al, 2007 ). On the other hand, certain child‐related factors such as ASD/impairment severity (e.g., greater impairments in the social, language, behavioral, or motor domains) or age (e.g., younger children) may be related to greater service needs (Green et al, 2006 ; Srinivasan, Ekbladh, et al, 2021 ; White et al, 2006 ). Taken together, different child and family characteristics will influence service utilization by families of children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Among demographic factors, belonging to minorities or lower SES were more associated with unmet needs (Farmer et al, 2004 ; Kogan et al, 2008 ). Among child‐related factors ASD severity, specifically, greater negative behaviors, lower language, functional, and motor abilities were associated with greater perceived unmet needs (Palisano et al, 2010 ; Douma et al, 2006 ; Srinivasan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of the child's communication and socialization skills, low ability for self-caring in daily routines, and societal barriers such as inadequate school system services to address needs and lack of other support resources may challenge families raising a child with ASD (Ho et al ., 2018 ). Due to the multifaceted nature of the disorder and lack of evidence-based treatment options, parents of autistic children are in a persistent search for services from multiple sources and specialists to address the needs of their children (An et al ., 2020 ; Srinivasan et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies from the US showed that despite greater utilization of services, caregivers of children with ASD were more likely to report difficulties in accessing child healthcare services and have more unmet family support needs as compared to caregivers of children with other developmental disabilities or typically developing children (Vohra et al ., 2014 ; Srinivasan et al ., 2021 ). Previous research from low and middle-income countries on children with ASD found challenges related to primary caregivers' needs for family support, accessibility for services and well-trained specialists, public awareness and understanding of autism, inclusive education system and social acceptance of children with ASD (Bilgin and Kucuk, 2010 ; Divan et al ., 2012 ; Tilahun et al ., 2016 ; Gobrial, 2018 ; Shorey et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Por último, además, también resulta más difícil para niños y adolescentes con autismo grave el acceso a las actividades de ocio durante los periodos de vacaciones escolares, lo que vuelve a redundar en un sobreesfuerzo familiar (10). Los recursos especializados en proporcionar estancias que permitan el descanso de las familias están saturados, y es frecuente que esta falta de accesibilidad favorezca hospitalizaciones psiquiátricas innecesarias (11,12).…”
unclassified